Discretionary Allowances in 1946–1997 - Szadkowska, Anna (Journal of Finance and Financial Law, 2015)
This article raise the issues of historical analysis of discretionary allowances in 1946–1997. An author refer to legal nature of allowances institution, which are connected with administrative approval, including the legal prerequisites of allowances granting, and influence of today policy and tax practice on legal form talked-about institutions. The aim of study is congeneric analysis of the grounds, which channel researched allowances to the present shape.